The overexpression of antifungal genes enhances resistance to rhizoctonia solani in transgenic potato plants without affecting arbuscular mycorrhizal symbiosis. (October 2019) - Fernandez Bidondo, L.; Almasia, N.; Bazzini, A.; Colombo, R.; Hopp, E.; Vazquez-Rovere, C.; Godeas, A.
Abstract: The biological control of fungal diseases through the use of genetically modified (GM) plants could decrease the input of chemical pesticides. To overcome possible losses in potato ( Solanum tuberosum ) yield because of susceptibility to soil fungal pathogens, researchers have developed potato transgenic lines expressing antifungal proteins. However, all GM crops must be monitored in their potentially detrimental effects on non-target soil microorganisms. Arbuscular mycorrhizal (AM) fungi are good candidates for this type of analysis, as good indicators of a normal rhizosphere structure and functionality. In this work, we have monitored potato lines with over-expression of genes encoding peptides with antifungal properties on their effects on the soil-borne fungal pathogen Rhizoctonia solani and AM fungi. The six GM potato lines (AG-1, AG-3, RC-1, RC-5, AGRC-8 and AGRC-12) evaluated showed higher reduction in infection indexes in comparison to untransformed plants when challenged with a highly virulent strain of R. solani . The growth of RC-1, RC-5 and AGRC-12 lines remained almost unaltered by the pathogen; which evidenced the maximum inhibition of R. solani infection. The level of root colonization by the AM fungus Rizophagus intraradices (pure in vitro isolated) did not significantly differ between transgenic and wild potato lines under in vitro and microcosm conditions. An increase in mycorrhization was evident with the addition of potato biomass residues of these GM lines in comparison to the addition of residues of the wild type potato line. In addition to the R. intraradices assays, we performed microcosm assays with soil samples from sites with at least100-year history of potato crop as inoculum source.The roots of AGRC-12 GM line showed significant higher levels of native mycorrhization and arbuscules development. In general, the potato lines apparently were less receptive to R. intraradices pure inoculum than to AM species from the natural inoculum. In this work, the selected GM potato lines did not have evident adverse effects on AM fungal colonization. Highlights: Potato transgenic lines expressing genes encoding antifungal proteins has been developed. These lines showed high reduction in infection indexes against Rhizoctonia solani . Rizophagus intraradices colonization did not differ between transgenic and wild potato. Addition of transgenic potato biomass residues increased mycorrhization. AGRC-12 transgenic line increased native mycorrhization and arbuscules development.